Innovation ambidexterity and knowledge redundancy: The moderating effects of transactional leadership - Duan, Yunlong; Liu, Wenjing; Wang, Shanshan; Yang, Meng; Mu, Chang (Frontiers in Psychology, 2022)
Entering the challenging and promising knowledge era, it is clear that enterprises should leverage knowledge management activities in improving innovation performance to maintain competitive advantages. This study sheds light on the improvement path of innovation ambidexterity (i.e., exploratory and exploitative innovation) from the perspectives of knowledge redundancy and typical leadership style. It is noted that we determined the research theme through quantitative analysis and conducted qualitative analysis through 209 questionnaire data collected from respondents in different regions and industries in China. The empirical results indicated that knowledge redundancy significantly improves exploratory and exploitative innovation, and transactional leadership negatively moderates the above relationships. This study is of managerial implications to encourage employees to fully master and apply the existing knowledge to strengthen their innovation abilities in value creation. We also contribute to the theories pertaining to knowledge management, innovation, and ambidexterity by providing a deeper understanding of the influencing mechanism of knowledge redundancy in innovation ambidexterity while elaborating on the indirect effects of transactional leadership.